Sedimentology and the facies architecture of the Ghaggar‐Hakra Formation, Barmer Basin, India: Implications for early Cretaceous deposition on the north‐western Indian Plate margin. (8th November 2018) - Beaumont, Hazel; Clarke, Stuart M.; Burley, Stuart D.; Taylor, Andrew M.; Mohapatra, Pinakadhar
Abstract: Fluvial strata of the Lower Cretaceous Ghaggar‐Hakra Formation are exposed in fault blocks on the central‐eastern margin of the Barmer Basin, Rajasthan. The sedimentology of these outcrops are described from 114 logs (thicknesses up to 100 m) and 53 two‐dimensional correlation panels. The formation comprises three distinct channel belt sandstone packages defined as the Darjaniyon‐ki Dhani, Sarnoo and Nosar sandstones separated by thick siltstone‐dominated floodplain successions. The sediments were deposited in a sub‐tropical, low sinuosity fluvial system that matures into a highly sinuous fluvial system. The Nosar Sandstone, the youngest of the three packages, exhibits a significant increase in energy and erosive power compared to those underlying it. This distinct change in fluvial style is interpreted as being rejuvenation due to an actively developing rift network forming accommodation space, rather than climatic controls acting on part of the depositional system. Consequently, the Ghaggar‐Hakra Formation at outcrop represents Lower Cretaceous syn‐rift deposition within the Barmer Basin with active localized fault movement from Nosar Sandstone times onward. These findings provide sedimentological evidence in support of pre‐Palaeogene northwest–southeast extension in the Barmer Basin. Moreover, they imply Cretaceous extension took place widely along the northern extremity of the West Indian Rift System consistent with plate tectonic models of the break‐up of Gondwana and evolution of the Indian Ocean. Outcrops of Lower Cretaceous strata are patchy across India and Pakistan. This study provides valuable material which, when combined with the available published data, facilitates a re‐evaluation of Lower Cretaceous palaeogeography for the north‐west Indian Plate. The reconstruction demonstrates a complex fluvial system, where the sediments are preserved sporadically as early syn‐rift strata. The findings imply a high preservation potential for early Cretaceous fluvial successions within rifted fault blocks near Saraswati and Aishwarya of the Barmer Basin beneath the Palaeogene fill that likely have significant potential for further hydrocarbon exploration. Abstract : This work summarises the previously unrecognised Ghaggar‐Hakra Formation of the Barmer Basin, in an attempt to help provide information for the development of the Lower Cretaceous palaeogeography of the northern margin of the Indian Plate.